Review of: Thomas W. Gallant, Νεότερη Ελλάδα: Από τον Πόλεμο της Ανεξαρτησίας μέχρι τις μέρες μας [Modern Greece: From the War of Independence to the Present], Athens: Pedio, 2017 - Gardikas, Katerina (The Historical Review/La Revue Historique, 2019)
.